Convenient synthesis of uncovered imprinted microspheres by Ganoderma lucidum spore-stabilized pickering emulsion polymerization and their enhanced recognition of spiramycin. Issue 60 (29th October 2019) - Zhu, Yanzhuo; Teng, Honghui; Sun, Dongshu; Jiang, Dayu; Yan, Yongsheng
Abstract : In this work, a new and simple method was developed for the synthesis of uncovered and high-selectivity spiramycin-based molecularly imprinted microspheres (SP-MIMs) by Pickering emulsion polymerization using spiramycin as templates. Abstract : In this work, a new and simple method was developed for the synthesis of uncovered and high-selectivity spiramycin-based molecularly imprinted microspheres (SP-MIMs) by Pickering emulsion polymerization using spiramycin as templates. And surprisingly the solid particles were absent on the surface of imprinted microspheres, which can be ascribed to the Ganoderma lucidum spores (GLS): they were firstly selected to be the stabilizers for the Pickering emulsion in this new strategy. Through a series of adsorption experiments, the uncovered SP-MIMs were proven to possess more excellent selective recognition and removal ability for template SP in aqueous solution. And SP-MIMs could be reused for many times without significant loss of adsorption capacity, indicating the satisfactory regeneration performance. Therefore, SP-MIMs can be employed as a promising adsorbent for the selective removal of SP from aqueous media, and this strategy will contribute to overcoming the shortcomings of stabilizer particles on the surface of the as-prepared imprinting microspheres, because these solid particles lack the special selective recognition activity of template molecules, and may disturb the adsorption effect of imprinting microspheres.